"Was ist das Volk?" : Volks- und Gemeinschaftskonzepte der politischen Mitte in Deutschland 1917-1924 - Retterath, Jörn 1983- (Quellen und Darstellungen zur Zeitgeschichte, 2016)
"What is the 'Volk'? The answers to this question matter greatly to a democracy. Does it involve an association between citizens as equals, a community of descent, or an underprivileged minority? Jörn Retterath analyzes the thinking of the German political mainstream, from the Social Democratic Party (SPD) to the German People's Party (DVP), on the nature of 'Volk' and community in Germany during the upheavals of 1917-1924"--Provided by publisher